EDBD-3,6-Epidioxy-1,10-Bisaboladiene-An Endoperoxide Sesquiterpene Obtained from Drimys brasiliensis (Winteraceae) Exhibited Potent Preclinical Efficacy against Schistosoma mansoni Infection - Eric Umehara; Thainá R. Teixeira; Rayssa A. Cajás; Monique C. Amaro; Josué de Moraes; João Henrique G. Lago (MDPI AG, 2024)
Schistosomiasis, a neglected tropical disease impacting over 250 million individuals globally, remains a major public health challenge due to its prevalence and significant impact on affected communities. Praziquantel, the sole available treatment, highlights the urgency of the need for novel anthelmintic agents to achieve the World Health Organization (WHO) goal of schistosomiasis elimination. Previous studies reported the promising antiparasitic activity of different terpenoids against Schistosoma mansoni Sambon (Diplostomida: Schistosomatidae). In the present work, the hexane extract from branches of Drimys brasiliensis afforded a diastereomeric mixture of endoperoxide sesquiterpenes, including 3,6-epidioxy-bisabola-1,10-diene (EDBD). This compound was evaluated in vitro and in vivo against S. mansoni. EDBD exhibited a significant reduction in S. mansoni viability in vitro, with an effective concentration (EC50) value of 4.1 µM. Additionally, EDBD demonstrated no toxicity to mammalian cells. In silico analysis predicted good drug-likeness properties, adhering to pharmaceutical industry standards, including favorable ADME profiles. Furthermore, oral treatment of S. mansoni-infected mice with EDBD (400 mg/kg) resulted in a remarkable egg burden reduction (98% and 99% in tissues and feces, respectively) surpassing praziquantel's efficacy. These findings suggest the promising potential of EDBD as a lead molecule for developing a novel schistosomiasis treatment.